The Association between Vitamin D Hypovitaminosis and Cardiovascular Disease Risk in Saudi Diabetic Patients Type II - Abeer Ahmed Alrefai; Elsayed Elsalamony; Sameer H. Fatani; Zeinab A. Kasemy; Abdulaziz Fatani; Hala Fawzy Mohamed Kamel (Biochemistry Research International)
We evaluated the prevalence and association of Vitamin D deficiency with glycemic control and CVD risk in T2DM patients. Serum 25 (OH)D3, lipid profile, glucose panel, HbA1c, serum insulin, and HOMA-IR were assessed in 93 T2DM patients and 69 controls. 10 years and lifetime ASCVD risk scores were calculated. The levels of 25(OH)D3 were significantly low in T2DM patients compared to the control. T2DM patients with hypovitaminosis D displayed significantly increased FBG, insulin, and HOMA-IR compared to normovitaminosis. Their lifetime and 10-year ASCVD risk scores were significantly higher regardless of vitamin D deficiency levels (P=0.006; P=0.023) in comparison to patients with sufficient levels of vitamin D. Among patients, the lifetime and 10 years of ASCVD risk showed a significant negative correlation with serum 25(OH)D3 and HDLc (P=0.037; 0.018) (P=0.0001), respectively, and significant positive correlation with T2DM duration, serum insulin, and HOMA-IR (P=0.018; 0.0001) (P=0.002; 0.001) (P=0.005; 0.001), respectively. The 10-year ASCVD risk exhibited a significant positive correlation with FBG (P=0.003) and HbA1c (P=0.009). T2DM duration was a predictor of vitamin D deficiency among T2DM patients (β = 0.22; CI = 0.002–0.04). There is a considerable association between lifetime and 10 years of ASCVD risk with hypovitaminosis D in T2DM, regardless of the deficiency levels which could be predicted by the diabetes duration.